Simplifying the Process for Finding Research Funding: A Cross-Campus Collaboration at a Large Academic Institution. Issue 1 (2nd January 2016) - Rosenzweig, Merle; Smith, Judith E.; Curtis, Ann; Puffenberger, Amy
ABSTRACT: This article describes the collaboration between the University of Michigan's M-Library and the University of Michigan Medical School's Office of Research in developing a comprehensive online guide and consultation service. The guide was designed to assist researchers in finding available funding from both internal and external sources and was based on the results of a survey distributed by the Office of Research. Because many of the respondents were unaware of internal funding programs and needed more information on resources external to the university as well, the guide included information on both possibilities in an easy-to-use format that researchers use independently without needing further instruction, although personal consultation was also offered when necessary.